Analysis of the Relationship between Age and Immunization Completeness with Measles Incidence in the City of Medan in 2022 - Harahap, Sunnii Irtiyah; Ismah, Zata; Hotmaida, Doris (International Journal of Integrated Health Sciences, 2024)
Objective: To analyze the relationship between age and immunization completeness and the occurrence of measles in Medan City in 2022.Methods: This study is quantitative research with a case-control study design. The respondents in this study are the entire population of Medan City. The sample size for this research is 96 respondents, with 48 in the case group and 48 in the control group, all recorded in the measles case report at the Health Department of Medan City in 2022. The study was conducted from January to July 2023.Results: Forty respondents in this study belonged to the toddler group, and most of whom had an incomplete immunization history. Based on chi-square analysis, a significant relationship was found between age and the occurrence of measles (p-value < 0.05), as well as between immunization completeness and the occurrence of measles (p-value < 0.05) with an odds ratio (OR) of 11.0. This means that respondents who are not immunized are 11 times more likely to experience measles compared to those who are immunized. Respondents with incomplete immunization are also 11 times more likely to experience measles compared to those with complete immunization.Conclusion: There is a significant relationship between age and immunization completeness and the occurrence of measles. Respondents with an incomplete immunization history are at 11 times higher risk of experiencing measles compared to those with a complete immunization history. For future research, it is recommended to increase the number of study respondents and further explore and expand on risk factors such as the history of contact with measles cases in the city of Medan.